Perilaku Mahasiswa terhadap Feminisme Perempuan Disabilitas dalam perspektif Hadis di UIN K.H Abdurrahman Wahid Pekalongan - Aulia Syahna, Ananda Aprilia (Takafu: Journal of Tafsir and Gender Perspective, 2024)
Women with disabilities have always been considered weak and underappreciated in various ways, resulting in the denial of their rights to education, health, employment, and justice. The viewpoint of feminism emanating from the west is not a strange entity for the east. This is actually considered good, we can even see this in the behavior of the Prophet, who showed humanist characteristics in women by respecting gender equality in various fields. This research is located at UIN KH Abdurrahman Wahid Pekalongan and describes issues of disability feminism and behavior in women with disabilities. The stages of research through data collection (observation, interviews, and documentation) are continued with data analysis and finally drawing conclusions. The results of this study show that the pattern of feminist behavior that occurs in women with disabilities does not all see them as weak, some even admire their determination, so that the existence of feminism does not limit women with disabilities from developing their talents. However, sometimes, with their limitations, they have no friends. One of the women with disabilities is always patient and enthusiastic about living her life. Closely related to the hadith of the Prophet Muhammad (peace be upon him), it is about respecting women on behalf of their wives and Muslim women in the early days of Islam with their rights in economic, social, positional, and other ways. Based on the analysis, it can be concluded that the Holy Prophet is a profile of a prophet who is feminist, non-discriminatory, humanist, and universal.